2020
DOI: 10.3390/jcs4020034
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Strength and Toughness of Hierarchical Composites through Optimization of Position and Orientation of Nanotubes: A Computational Study

Abstract: Hierarchical composites that combine microscopic fibers and carbon nanotubes (CNTs) offer opportunities to further improve mechanical properties. Motivated by the experimental evidence that the spatial distribution of CNTs has a significant effect on the strength and toughness of these composites, we developed a novel modelling tool to help us explore mechanisms of strengthening and toughening in an efficient way. The spatial position and orientation of CNTs are chosen as design variables and their optimizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…CFR‐C2 has the minimum wear rate among the four composites. The specific reason for the improvement in wear resistance can be attributed to three aspects: (i) MWCNT increase the mechanical interlocking between fiber and matrix, enhancing the wear resistance; (ii) MWCNT/carbon fabric multi‐scale hybrid materials play synergistic effects between nano‐scale MWCNT and micro‐scale carbon fiber reinforcements 30 ; (iii) friction film could be formed during the friction process, providing wear protection and increasing the surface lubrication 31 . Besides, the wear rate of CFR‐C3 slightly increase compared with that of CFR‐C2.…”
Section: Resultsmentioning
confidence: 99%
“…CFR‐C2 has the minimum wear rate among the four composites. The specific reason for the improvement in wear resistance can be attributed to three aspects: (i) MWCNT increase the mechanical interlocking between fiber and matrix, enhancing the wear resistance; (ii) MWCNT/carbon fabric multi‐scale hybrid materials play synergistic effects between nano‐scale MWCNT and micro‐scale carbon fiber reinforcements 30 ; (iii) friction film could be formed during the friction process, providing wear protection and increasing the surface lubrication 31 . Besides, the wear rate of CFR‐C3 slightly increase compared with that of CFR‐C2.…”
Section: Resultsmentioning
confidence: 99%
“…By filling epoxy resins with carbon nanotubes, the strength properties of the resulting nanocomposite can be modifieddepending on the resin and nanotubes used. According to Ciecierska et al (2015), Ganesh et al (2017), andLiu et al (2020), the highest strength of the obtained nanocomposite is observed at a content of 0.1%-0.5% by weight of nanotubes, and according to the work (Smoleń et al, 2021) at a content of 1.5%. Increasing the amount of nanofiller added results in a decrease in the strength of the material.…”
Section: Introductionmentioning
confidence: 84%
“…Other finite element modeling [ 143 ] at dual‐scales demonstrated four failure types in CNT‐grafted FRPs using the CNT tensile strength and CNT/matrix interfacial strength as a means of comparison. The four failure modes are listed as follows: (I) denoted low CNT‐matrix interfacial strength that led to excessive CNT debonding from the fiber and fiber debonding; (II) CNTs partially debonding and matrix cracking, (III) CNT debonding, fiber debonding, and CNT detachment simultaneously, and (IV) fiber debonding and then CNT debonding.…”
Section: Mechanical Properties Of Cnt‐frps: Modeling and Mechanismsmentioning
confidence: 99%
“…These events can significantly enhance the toughness of FRPs. [ 99,143 ] In particular, analytical research has revealed that crack bridging by CNTs and their subsequent fracture can contribute considerably to increases in the interlaminar fracture toughness of the CNT‐FRPs. [ 152 ] CNT bridging can also induce crack deflection [ 146 ] and prevent delamination, [ 153 ] which provides significant energy absorption during the fracture of FRPs.…”
Section: Toughening Mechanisms In Cnts‐frpsmentioning
confidence: 99%